(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article discusses the organizational and methodological aspects of the implementation of the international financial reporting standard IAS 41 "Agriculture" in Uzbekistan. Special attention is paid to the analysis of the current state of accounting in the agricultural sector, the identification of problems related to the transition to international standards, as well as proposals for solving these problems agricultural enterprises, will improve the management of biological assets and open up new opportunities for attracting investment and developing the agricultural sector. The article also highlights the need to update the regulatory framework, introduce digital solutions and improve the skills of accountants to successfully adapt to international standards.